Synthetic Studies on Tricyclic Diterpenoids: Direct Allylic Amination Reaction of Isopimaric Acid Derivatives1. Issue 1 (28th October 2015) - Timoshenko, Mariya A.; Kharitonov, Yurii V.; Shakirov, Makhmut M.; Bagryanskaya, Irina Yu.; Shults, Elvira E.
Abstract: A selective synthesis of 7‐ or 14‐nitrogen containing tricyclic diterpenoids was completed according to a strategy in which the key step was the catalyzed direct allylic amination of methyl 14α‐hydroxy‐15, 16‐dihydroisopimarate with a wide variety of nitrogenated nucleophiles. It was revealed that the selectivity of the reaction depends on the nature of nucleophile. The catalyzed reaction of the mentioned diterpenoid allylic alcohol with 3‐nitroaniline, 3‐(trifluoromethyl)aniline, and 4‐(trifluoromethyl)aniline yield the subsequent 7α‐, 7β‐ and 14αnitrogen‐containing diterpenoids. The reaction with 2‐nitroaniline, 4‐nitro‐2‐chloroaniline, 4‐methoxy‐2‐nitroaniline, phenylsulfamide, or tert ‐butyl carbamate proceeds with the formation of 7α‐nitrogen‐substituted diterpenoids as the main products. Abstract : We have demonstrated that the gold‐catalyzed amination of isopimaric acid derivatives with substituted anilines, benzenesulfonamide, or tert ‐butyl carbamate produces good to excellent yields of nitrogen‐containing tricyclic diterpenoids, which are extremely useful synthetic intermediates in the construction of biologically important compounds. The stereochemical result of the reaction is dependent on the nature of the nucleophile.